Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/ejhg.2016.197
|View full text |Cite
|
Sign up to set email alerts
|

Suggestive association between variants in IL1RAPL and asthma symptoms in Latin American children

Abstract: Several genome-wide association studies have been conducted to investigate the influence of genetic polymorphisms in the development of allergic diseases, but few of them have included the X chromosome. The aim of present study was to perform an X chromosome-wide association study (X-WAS) for asthma symptoms. The study included 1307 children of which 294 were asthma cases. DNA was genotyped using 2.5 HumanOmni Beadchip from Illumina. Statistical analyses were performed in PLINK 1.9, MACH 1.0 and Minimac2. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Previous studies have identified genetic, environmental, behavioral, and socioeconomic factors associated with the development of allergic diseases in childhood, likely to reflect complex interactions between genes and environmental exposures [38], [39,40]. Genetic studies have identified polymorphisms associated with both atopic and non-atopic asthma [27,41,42], highlighting the importance of family history as a risk factor. Bjerg.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified genetic, environmental, behavioral, and socioeconomic factors associated with the development of allergic diseases in childhood, likely to reflect complex interactions between genes and environmental exposures [38], [39,40]. Genetic studies have identified polymorphisms associated with both atopic and non-atopic asthma [27,41,42], highlighting the importance of family history as a risk factor. Bjerg.…”
Section: Plos Onementioning
confidence: 99%
“…Yang and colleagues [40] identified 81 regions on the genome that were differentially methylated in asthmatic children aged between 6 and 12 years. Further studies to identify polymorphisms and epigenetic alterations associated with allergic diseases, as well as variants in genes associated with reduced pharmacologic response, are required for a better understanding of asthma and its treatment among Andean children with asthma [41,[46][47][48][49].…”
Section: Plos Onementioning
confidence: 99%
“…Eight GWAS evaluated the association with asthma (33, 35, 37, 38, 4244, 46) (Supplementary Table 1), although only four studies revealed genome-wide significant associations (38, 43, 44, 46). These validated the association of 14 loci previously associated with asthma susceptibility (Table 1).…”
Section: Genome-wide Association Studiesmentioning
confidence: 99%
“…In fact, it has been proposed that PRS estimation could facilitate the development of accurate preventive, diagnostic and therapeutic strategies (223, 227, 236). Moreover, given the previous evidence of genetic overlap among different diseases (35, 45, 49, 103, 227, 237), an evaluation of individual risks could be assessed simultaneously for multiple traits at a time. This would potentiate the implementation of common therapeutic strategies for different diseases (227, 236).…”
Section: Asthma Prediction and Translation Into The Clinicmentioning
confidence: 99%
“…Much more compelling is the need for a more global distribution of research groups with a strong background in genomics and bioinformatics, leading and performing this kind of study. In this context, the overarching goal of the EPIGEN-Brazil Initiative is to study the genomic diversity and its effects on complex phenotypes in Brazil, the most populous Latin American country (Borges et al 2016;Lima-Costa et al 2016;Marques et al 2017). Brazil's more than 200 million inhabitants are the product of admixture that occurred during the last 500 years between Amerindians, Europeans, Africans, and their descendants.…”
mentioning
confidence: 99%